STRATEGY OF THE INVESMENT AND ONE-STOP INTEGRATED SERVICE OFFICE (DPMPTSP) IN INCREASING BUSINESS IDENTIFICATION NUMBER (NIB) OWNERSHIP FOR MSMEs IN SUKABUMI CITY - Dhani Firmansyah; Dian Purwanti; Tuah Nur (Proceedings International Indonesia Conference on Interdisciplinary Studies, 2025)
Business legality is an important foundation in strengthening the position of Micro, Small, and Medium Enterprises (MSMEs) amid the ever-evolving digital economy ecosystem and public policies. However, the low rate of Business Identification Number (NIB) ownership among MSME operators remains a challenge in many regions. This study aims to analyze the strategies employed by the Investment and Integrated One-Stop Service Agency (DPMPTSP) of Sukabumi City in promoting systematic and sustainable increases in NIB ownership. The approach used is descriptive qualitative, employing Everett Rogers' innovation diffusion theory as the analytical framework, encompassing four main dimensions: innovation, communication channels, time, and social systems. The research findings indicate that public service innovations such as the SI JIMAT BOSS program (Ready to Pick Up Permits in the Community Together with OSS) have successfully brought licensing services directly to the community through a proactive approach. The effectiveness of this strategy is reflected in the achievement of 97.47% of SMEs in Sukabumi City having obtained an NIB by 2024. In addition to reducing service time, the DPMPTSP has maximized multi-platform communication channels and fostered cross-sectoral collaboration. These results indicate that adaptive, participatory, and locally-driven strategies can accelerate business legalization and strengthen the competitiveness of SMEs. This study provides practical contributions as a best practice reference for inclusive and innovation-based local licensing service management. Keywords: strategy, SMEs, NIB, DPMPTSP Sukabumi City, Innovation Diffusion, Public Services, Best Practice.